Adult dural arteriovenous fistulas in Galen region: More to be rediscovered - Tu, Tianqi; Song, Zihao; Ma, Yongjie; Yang, Chengbin; Su, Xin; He, Chuan; Li, Guilin; Hong, Tao; Sun, Liyong; Hu, Peng; Zhang, Peng; Ye, Ming; et al. (Frontiers in Neurology, 2022)
Background Dural arteriovenous fistulas (DAVFs) in the Galen region are the most deeply located and most complex type of dural arteriovenous fistulas. However, cases of DAVFs in this region have not been well described. Thus, we aimed to summarize the characteristics of Galenic DAVFs involving clinical symptoms, anatomical architecture, and drainage patterns, providing experientially therapeutic strategies for these lesions based on our 20 years of clinical experience. Methods We retrospectively examined 31 patients with Galenic DAVFs between January 2000 and June 2021. A comprehensive analysis was carried out based on the symptoms, imaging features, feeding arteries, draining veins, number and location of the fistulas, choice of treatment methods, and prognosis assessment. Results Twenty-nine patients received endovascular embolization, and no perioperative deaths occurred. A transarterial approach was performed in 27 patients, and a combined transarterial and transvenous approach in one. And in one case, access was established by surgical drilling and embolization was done via the venous route. Twenty-four cases were completely obliterated after first embolization, and another five cases received a second period treatment. Only one patient developed cognitive dysfunction after embolization, and the outcomes of the remaining patients were improved at long-term follow-up. Conclusion The understanding of symptoms of non-hemorrhagic neurological deficits in DAVF needs to be further clarified. Lesions with pial feeders may be considered first when determining surgical orders. Multi-approach and multi-stage embolization would be safe and effective. Excessive embolization and deep-vein system obstruction should be avoided. Approach creation by surgery would be an innovative interventional therapy.